Foreign Direct Investment, Real Effective Exchange Rate and China’s Economy - Lin, N.; Pan, X. (Journal of Comparative International Management)

(untitled) (Management Futures, 2006)
Changes in China’s Balance of Payment (BOP) reveal that integration between China and the outside world is much closer. On the basis of these BOP changes, this paper examines Foreign Direct Investment (FDI) and Real Effective Exchange Rate (REER) in China because of their importance in economic growth. A number of important issues that may underlay China’s economy imbalance are discussed, and it is suggested that current account surpluses and FDI remain important contributors to the foreign exchange reserve accumulation. Using empirical methodology analysis, the relationships and interactions between FDI, REER and Gross Domestic Product (GDP) in China in the long-run is shown, which yield additional information about implications for the behaviors of REER and FDI in the Chinese economy.